2020
DOI: 10.1021/acs.energyfuels.0c02690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Charge Density of Reverse Emulsion Breaker on Demulsification Performance for Steam-Assisted Gravity Drainage (SAGD) Emulsions under High Temperature and High Pressure

Abstract: Reverse emulsion breakers (REBs) play a crucial role in the demulsification of complex water-in-oil-in-water (W/O/ W) emulsions in steam-assisted gravity drainage (SAGD) production of oil sands. Developing effective REBs remains challenging due to the poor understanding of influencing factors and demulsification mechanisms. In particular, despite the recognition of the vital role of charge density of the REBs in their demulsification performance, the available literature is limited. Herein, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Rocha et al (2018) found that the least soluble fraction of asphaltenes acted as a stabilized agent for water in bitumen emulsions . Wang et al (2020) measured a charge density of a reverse emulsion breaker to find a suitable agent to break emulsion in SAGD operation conditions . Velayati and Nouri in 2020 presented a review on emulsification and emulsion flow during a SAGD process, which covered emulsification mechanisms, emulsion stability, emulsion properties, and controlling factors on emulsion formation …”
Section: Steam-assisted Gravity Drainage (Sagd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Rocha et al (2018) found that the least soluble fraction of asphaltenes acted as a stabilized agent for water in bitumen emulsions . Wang et al (2020) measured a charge density of a reverse emulsion breaker to find a suitable agent to break emulsion in SAGD operation conditions . Velayati and Nouri in 2020 presented a review on emulsification and emulsion flow during a SAGD process, which covered emulsification mechanisms, emulsion stability, emulsion properties, and controlling factors on emulsion formation …”
Section: Steam-assisted Gravity Drainage (Sagd)mentioning
confidence: 99%
“…139 Wang et al (2020) measured a charge density of a reverse emulsion breaker to find a suitable agent to break emulsion in SAGD operation conditions. 140 Velayati and Nouri in 2020 presented a review on emulsification and emulsion flow during a SAGD process, which covered emulsification mechanisms, emulsion stability, emulsion properties, and controlling factors on emulsion formation. 141 Steam injection is an effective way to reduce oil viscosity, but it also raises the reservoir temperature leading to H 2 S and CO 2 generation by aquathermolysis.…”
Section: ■ Css Follow-up Processes and Simulationmentioning
confidence: 99%
“…To deal with inaccessible placements or uncommon compositions of unconventional resources, innovative production techniques and novel approaches seem to be necessary. For heavy and extra-heavy oil reservoirs, thermal methods are primarily used methods due to their capability to decrease oil viscosity and increase its mobility. Generally, thermal EOR (ThEOR) methods consist of steam-assisted gravity drainage, , cyclic steam stimulation, , and in situ combustion (ISC) , methods. However, a literature review on ThEOR methods proposed the ISC technique to be one of the most energy-efficient processes which can improve the properties of heavy oil through decreasing heavy components such as asphaltene and resins. , In the ISC process, air/oxygen is injected into the reservoir to generate heat by burning a portion of the hydrocarbons that leads to a heat front in the reservoir, which reduces the viscosity of heavy and extra-heavy oils and sometimes achieves conditions for in situ upgrading, thereby EOR .…”
Section: Introductionmentioning
confidence: 99%
“…For heavy and extra-heavy oil reservoirs, thermal methods are primarily used methods due to their capability to decrease oil viscosity and increase its mobility. 1−3 Generally, thermal EOR (ThEOR) methods consist of steam-assisted gravity drainage, 4,5 cyclic steam stimulation, 6,7 and in situ combustion (ISC) 8,9 methods. However, a literature review on ThEOR methods proposed the ISC technique to be one of the most energy-efficient processes which can improve the properties of heavy oil through decreasing heavy components such as asphaltene and resins.…”
Section: Introductionmentioning
confidence: 99%
“…Among the current emulsion treatment methods, e.g., microwave irradiation, centrifugation, hydrocyclone, and chemical demulsification, chemical treatment is extensively applied in consideration of its cost-efficiency and effectiveness. To promote the chemical demulsification efficiency, a special focus was generally placed on the development of effective demulsifiers by employing model emulsions. Nevertheless, the characteristics of practical emulsions, such as compositions, particle size distribution, and component interactions, have significant and various effects on the demulsification efficiency. , The precise and comprehensive correlation between the characteristics of practical bitumen froth and the demulsification efficiency has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%